UPAYA PENINGKATAN PRESTASI BELAJAR SISWA PADA MATERI MATRIKS DENGAN MODEL KOOPERATIF TIPE JIGSAW DI SMK NEGERI 1 TEBO - ERMAWATI ERMAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve student achievement in Mathematics lessons with the Jigsaw type cooperative learning model at SMK Negeri 1 Tebo, Tebo Regency, Jambi Province, for the 2019/2020 school year. The research method used in this research is Classroom Action Research (CAR). Classroom Action Research (CAR) with a systematic presentation of efforts to improve the implementation of educational practices by teachers and collaborators by taking actions in learning, based on reflections on the results of actions to achieve KKM. The subject of this research is class X AKT-B at SMK Negeri 1 Tebo, Tebo Regency, Jambi Province, totaling 35 students, consisting of 28 students and 7 students. The application of the jigsaw type cooperative learning model has good implications for improving students' cognitive and affective learning achievement of Mathematical Matrix material, based on observations by observers of student activities in participating in Mathematics learning Matrix material in the first cycle of student activity achieving an average value of 5 out of 11 indicators and increased in cycle II the average value of 10 out of 11 indicators. Increasing student achievement in learning mathematics using the jigsaw type of cooperative learning model, evidenced by an increase in student learning mastery from the first cycle to the second cycle, namely a significant increase in student learning mastery between cycle I (39%) to cycle II (86 %) which is equal to (86%-39%) = 45%. ABSTRAKPenelitian ini bertujuan untuk meningkatkan prestasi belajar siswa pada pelajaran Matematika materi Matriks dengan model pembelajaran kooperatif tipe Jigsaw di SMK Negeri 1 Tebo Kabupaten Tebo Provinsi Jambi tahun pelajaran 2019/2020. Metode penelitian yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK). Penelitian Tindakan Kelas (PTK) dengan penyajian sistimatika dari upaya perbaikan pelaksanaan praktek pendidikan oleh guru dan kolabolator dengan melakukan tindakan-tindakan dalam pembelajaran, berdasarkan refleksi mengenai hasil dari tindakan-tindakan untuk tercapainya KKM. Subjek penelitian ini adalah kelas X AKT-B di SMK Negeri 1 Tebo Kabupaten Tebo Provinsi Jambi yang berjumlah 35 siswa, terdiri dari 28 siswi dan 7 siswa. Penerapan model pembelajaran kooperatif tipe jigsaw berimplikasi baik terhadap peningkatkan prestasi belajar matematika materi Matriks secara kognitif dan afektif siswa, berdasarkan pengamatan oleh observer aktivitas siswa dalam mengikuti pembelajaran matematika materi Matriks pada siklus pertama aktivitas siswa mencapai nilai rata-rata dari nilai 5 dari 11 indikator dan meningkat pada siklus II nilai rata-rata sebesar 10 dari 11 indikator. Peningkatan prestasi belajar siswa dalam pembelajaran matematika materi Matriks dengan menggunakan model pembelajaran kooperatif tipe jigsaw, dibuktikan dengan adanya peningkatan ketuntasan belajar siswa dari siklus pertama ke siklus kedua, yakni meningkatnya ketuntasan belajar siswa yang signifikan antara siklus I (39%) ke siklus II (86%) yaitu sebesar (86%-39%) = 45%.